Tinjauan Nilai-Nilai Pemasaran Islam terhadap Pelaksanaan Komunikasi Pemasaran pada Kegiatan Penerimaan Santri Baru - Fahmi Ichsan Firdaus; Zia Firdaus Nuzula (Jurnal Riset Ekonomi Syariah, 2023)
Abstract. Al Ittifaq Islamic Boarding School implements an integrated marketing communication strategy in the new students admission program which must be based on Islamic marketing values. Based on this, the research focus is formulated in the form of the following questions: What are the concepts and values of marketing communications according to Islamic Marketing theory? How is the marketing communication strategy in increasing the number of new students accepted by the Al Ittifaq Ciwidey Islamic Boarding School, Bandung Regency? And what about the review of Islamic marketing values on the implementation of marketing communications in the activities of accepting new students at the Al Ittifaq Islamic Boarding School, Bandung Regency? The research method used is analytical descriptive and data sources obtained from observations, interviews and literature studies with qualitative data analysis techniques. The results showed that the concept of marketing communication according to Islamic marketing is the planning and implementation of elements in marketing communications consisting of advertising, direct response, sales promotion, public relations, and personal selling in accordance with Islamic teachings. The implementation of marketing communications at Al-Quran Al-Ittifaq Islamic Boarding School, Bandung Regency is carried out by using all elements of marketing communications in an integrated manner. Then the implementation of marketing communications in increasing the number of new student admissions applied to the Al Ittifaq Islamic Boarding School in Bandung Regency consisting of advertising, direct response, sales promotion, public relations, and personal selling is in accordance with Islamic marketing values. Abstrak. Pesantren Al Ittifaq menerapkan strategi komunikasi pemasaran terpadu dalam program penerimaan santri baru yang harus disandarkan pada nilai-nilai pemasaran Islam. Berdasarkan hal tersebut tersebut, maka fokus penelitian dirumuskan ke dalam bentuk pertanyaan berikut: Bagaimana konsep dan nilai-nilai komunikasi pemasaran menurut teori Pemasaran Islam? Bagaimana strategi komunikasi pemasaran dalam meningkatkan jumlah penerimaan santri baru yang dilakukan Pesantren Al Ittifaq Ciwidey Kabupaten Bandung? Dan bagaimana tinjauan nilai-nilai pemasaran Islam terhadap pelaksanaan komunikasi pemasaran pada kegiatan penerimaan santri baru di Pesantren Al Ittifaq Kabupaten Bandung? Metode penelitian yang digunakan adalah deskriptif analitis dan sumber data didapatkan dari hasil observasi, wawancara dan studi kepustakaan dengan teknik analisa data kualitatif. Hasil penelitian menunjukkan Konsep komunikasi pemasaran menurut pemasaran Islam adalah perencanaan dan pelaksanaan unsur-unsur dalam komunikasi pemasaran yang terdiri dari advertising, direct response, sales promotion, public relation, dan personal selling yang sesuai dengan ajaran Islam. Pelaksanaan komunikasi pemasaran pada Pesantren Al Quran Al Ittifaq Kabupaten Bandung dilakukan dengan menggunakan seluruh unsur komunikasi pemasaran secara terpadu. Kemudian pelaksanaan komunikasi pemasaran dalam meningkatkan jumlah penerimaan santri baru yang diterapkan pada Pesantren Al Ittifaq Kabupaten Bandung terdiri dari advertising, direct response, sales promotion, public relation, dan personal selling telah sesuai dengan nilai-nilai pemasaran Islam.